Computational algorithmic and molecular dynamics study of functional and structural impacts of non-synonymous single nucleotide polymorphisms in human DHFR gene. (December 2021) - Alam, Md. Shahed; Saleh, Md. Abu; Mozibullah, Md.; Riham, Ashik Tanvir; Solayman, Md.; Gan, Siew Hua
Abstract: Human dihydrofolate reductase (DHFR) is a conserved enzyme that is central to folate metabolism and is widely targeted in pathogenic diseases as well as cancers. Although studies have reported the fact that genetic mutations in DHFR leads to a rare autosomal recessive inborn error of folate metabolism and drug resistance, there is a lack of an extensive study on how the deleterious non-synonymous SNPs (nsSNPs) disrupt its phenotypic effects. In this study, we aim at discovering the structural and functional consequences of nsSNPs in DHFR by employing a combined computational approach consisting of ten recently developed in silico tools for identification of damaging nsSNPs and molecular dynamics (MD) simulation for getting deeper insights into the magnitudes of damaging effects. Our study revealed the presence of 12 most deleterious nsSNPs affecting the native phenotypic effects, with three (R71T, G118D, Y122D) identified in the co-factor and ligand binding active sites. MD simulations also suggested that these three SNPs particularly Y122D, alter the overall structural flexibility and dynamics of the native DHFR protein which can provide more understandings into the crucial roles of these mutants in influencing the loss of DHFR function. Graphical Abstract: ga1 Highlights: Dihydrofolate reductase (DHFR) is the key enzyme involved in folate metabolism. Many abnormalities including drug resistance arise due to the mutation in DHFR gene. Bioinformatics tools have been applied for both structural and functional analyses of the nsSNPs. Among the twelve highly deleterious nsSNPs, three mutants were found in the active site. Mutant Y122D significantly disrupts the native structure of the protein.